Uncovering Developing Countries’ Performance in Trade in Services - Saez, Sebastian; Goswami, Arti Grover (World Bank, Washington, DC, 2012)
Services play a broad and strategic role in the economy. Trade in services has been expanding rapidly because technological improvements have reduced the cost of cross-border exchange from infinity to virtually zero, thereby allowing for new export activities. Trade in services, particularly business services, has become an element of export diversification for many developing countries. Besides traditional activities such as tourism, activities such as health and information and communication services are among the most successful services exports. This note focuses on the determinants of trade in services for developing countries.